Exploring Motivational Factors for Educational Reform: Do International Comparisons Dictate Educational Policy? - AJ Stachelek (Journal of Mathematics Education at Teachers College, 2010)
In mathematics education, utilizing international comparisons to support implementation of educational reforms has become increasingly common. With the advent of Trends in International Mathematics and Science Study (TIMSS), educational reform seems to have transitioned to a reactionary process rather than a calculated adaptation of current educational systems. These policy changes may be in response to a need to demonstrate international superiority, determined by these standardized tests. This paper explores the history of educational reform in Japan and Singapore to investigate possible connections between achievement levels and reforms each country made to their educational systems. Frank’s Framework will be used to guide the analysis of their educational policies with a focus on how these countries use aspects of this framework to guide reform decisions, or if they use a narrow focus on the TIMSS results. These results can then be extended to the process of reform development in the United States.